Large-scale dinoflagellate bloom species Prorocentrum donghaiense and Karenia mikimotoi reduce the survival and reproduction of copepod Calanus sinicus. (11th May 2015) - Lin, Jia-Ning; Song, Jing-Jing; Yan, Tian; Zhang, Qing-Chun; Zhou, Ming-Jiang
Abstract : Large-scale blooms of dinoflagellates, such as Prorocentrum donghaiense and Karenia mikimotoi, have occurred frequently in the East China Sea (ECS) in recent decades. However, little is known about their effects on the entire life history of copepods. Under laboratory conditions, we investigated the effects of these two common dinoflagellates on the survival of Calanus sinicus individuals at different stages and on reproduction of this copepod. Compared with the control treatment ( Skeletonema costatum ), the presence of P. donghaiense and K. mikimotoi decreased the survival rates of adults and nauplii during the 16 days of the experiment. Survival of nauplii decreased to 49% and 48%, respectively, relative to the nearly 80% survival of adults. Among the six stages of nauplii, individuals at NII and NIII were more susceptible to P. donghaiense and K. mikimotoi . Lower egg production rates were also observed when copepods were exposed to P. donghaiense and K. mikimotoi, and hatching success decreased only with exposure to P. donghaiense . These results suggest that blooms of the two common dinoflagellates may have detrimental effects on the survival of nauplii and the reproduction of C. sinicus, which may pose a major threat to the recruitment of C. sinicus .